Comparing the Tibial Tuberosity–Trochlear Groove Distance Between CT and MRI in Skeletally Immature Patients With and Without Patellar Instability. Issue 1 (27th January 2021) - Dai, Zhen-Zhen; Sha, Lin; Zhang, Zi-Ming; Liang, Zhen-Peng; Li, Hao; Li, Hai
Background: The tibial tubercle–trochlear groove (TT-TG) distance was originally described for computed tomography (CT), but it has been measured on magnetic resonance imaging (MRI) in patients with patellar instability (PI). Whether the TT-TG measured on CT versus MRI can be considered equivalent in skeletally immature children remains unclear. Purpose: To investigate in skeletally immature patients (1) the effects of CT versus MRI imaging modality and cartilage versus bony landmarks on consistency of TT-TG measurement, (2) the difference between CT and MRI measurements of the TT-TG, and (3) the difference in TT-TG between patients with and without PI. Study Design: Cross-sectional study; Level of evidence, 3. Methods: We retrospectively identified 24 skeletally immature patients with PI and 24 patients with other knee disorders or injury but without PI. The bony and cartilaginous TT-TG distances on CT and MRI were measured by 2 researchers, and related clinical data were collected. The interrater, interperiod (bony vs cartilaginous), and intermethod (CT vs MRI) reliabilities of TT-TG measurement were assessed with intraclass correlation coefficients. Results: The 48 study patients (19 boys, 29 girls) had a mean age of 11.3 years (range, 7-14 years). TT-TG measurements had excellent interrater reliability and good or excellent interperiod reliability but fair or poor intermethod reliability. TT-TG distance was greater on CT versus MRI (mean difference, 4.07 mm; 95% CI, 2.6-5.5 mm), and cartilaginous distance was greater than bony distance (mean difference, 2.3 mm; 95% CI, 0.79-3.8 mm). The TT-TG measured on CT was found to increase with the femoral width. Patients in the PI group had increased TT-TG distance compared with those in the control group, regardless of landmarks or modality used ( P > .05 for all). Conclusion: For skeletally immature patients, the TT-TG distance could be evaluated on MRI, regardless of whether cartilage or bony landmarks were used. Its value could not be interchanged with CT according to our results; however, further research on this topic is needed.